Efektivitas Model Project Based Learning Era Merdeka Belajar dalam Meningkatkan Hasil Belajar Mahasiswa - Teza, Serli Diovani; Astuti, Widya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to see the effectiveness of the implementation of Project Based Learning (PjBL) to improve student learning achievement in the independent curriculum era. This study used 30 students in the fifth semester who were attending computer accounting lectures. Sampling technique using total sampling. The method used is a quasi-experiment (Quasi Experiment). The design in this study uses a posttest control group design with a non-equivalent group. In this study, data collection was carried out after treatment (posttest). Posttest data was analyzed descriptively with Anova to find out the difference between the experimental group and the control group. The results of the hypothesis test stated that there was a difference in learning outcomes between students who were taught with PjBL learning compared to students who were taught with conventional learning with the tutorial method. In conclusion, the project-based learning model is effective in improving student learning outcomes